Peranan Karang Taruna dalam Meningkatkan Kepedulian Sosial Masyarakat di dusun Sumber Rejo Bengkulu - Indriyani, Ririn; Afrika, Wina; Yulandari, Gusti; Purwaningsih, Purwaningsih; Hafis, Nur; Agustin, Erta; Saepudin, Saepudin (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research uses a qualitative research method with a descriptive approach. The location of this research was in Lokasi Baru Village, Air Periukan District, Seluma Regency. The subject of this research is the youth organization in Lokasi Baru Village. The data collection techniques used in this research are observation, interview, and documentation techniques. The role of youth organizations in increasing social care in the younger generation and the people of Lokasi Baru Village is running well, it can be seen from the activities of youth organizations in the village. The youth organization provides motivation about the importance of social care among the village community and invites the community to participate in social activities carried out by the youth organization. Thus, it can foster awareness of social care attitudes in the community. can be seen from the existence of supporting factors in social care activities carried out by youth organizations, namely the desire of members to carry out social care activities and community participation in social care activities. While the inhibiting factors of social care activities are the lack of awareness to fully contribute to every activity carried out by the youth organization, and the number of youth organization members who are still in school and already working and the lack of income for activities.